Generation of continuous variable Einstein-Podolsky-Rosen entanglement via the Kerr nonlinearity in an optical fibre - Leuchs, Gerd; et al. (Physical Review Letters, 2001)
A report on generation of a continuous variable Einstein-Podolsky-Rosen (EPR) entanglement was presented using an optical fiber interferometer. Two independent squeezed beams were generated using Kerr nonlinearity. ERP entanglement was obtained between the output beams. Correlation of amplitude quadratures was measured below the quantum noise limit.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.optik.1optik.genera